Por que Medicina? Por que UFSCar? Um registro da minha trajetória - Pereira, Rafaela Catelan Martins (Universidade Federal de São Carlos, 2020)
Introduction The Bachelor of Medical Sciences Degree at the Federal University of São Carlos (UFSCar) is based on developing the competence and the theoretical-practical integration by means of a constructivist educational approach and using active learning methodologies. As part of the students’ assessment, the Independent Study consists of a synthesis about the development of the professional experience during the course. Objectives The Independent Study general objective is to show and to share to the university community the log of clinical activities developed, the preceding expectations before the graduation, the understanding about health and care developed during the university undergraduate course, and the expectations at the end of the course regarding the professional experience. On the other hand, this Independent Study specific objective is to present insights about each educational term, such as: holistic approach to human care I, II and III, in areas of education – extension – research. Materials and methods Using the case assessment portfolio developed during the undergraduate course at the university, the author presents her personal opinion about the professional development process using an inquisitive narrative. Discussion The educational cycles (terms)progress were recorded balancing the three elements of the education-research-extension triad. The medical training becomes complete by enabling the union of formal classroom education – in which theory is closely connected to the practical experience -, the development of the bibliographic review and refined research and the construction of knowledge using scientific research. Activities that enabled integration between the university and society were also developed resulting in higher exposure of scientific production to the general public. Conclusion The educational, assistance and research elements of the undergraduate course programme are fundamental for the systematization of the professional development, aiding the student with the tools that will enable him/her to further develop clinical assessment skills, as well as developing and planning for the medical career.
Why Medicine? Why UFSCar? Reporting my journey
Keywords: Medicina; Graduação médica; Saúde; Cuidado em saúde; CIENCIAS DA SAUDE